Analisis Break-Event Point (BEP) dalam Produksi Clorot Cemethut Purworejo Sebagai dasar Penetapan Harga dan Volume Produksi Optimal - Dewi Yuliyanti; Hesti Respatiningsih; Anes Arini (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the Break-Even Point (BEP) of Clorot Cemethut MSMEs in Purworejo during 2022-2024 as a basis for pricing and production optimization. Quantitative descriptive methods are used to calculate BEP, Margin of Safety (MoS), and optimal production volume. The results show fluctuations in BEP and MoS each year which are influenced by fixed costs, variables, and sales. Variations in production BEP indicate the minimum amount of sales required so that MSMEs do not suffer losses. MoS increased rapidly in 2024, providing flexibility in pricing strategy. It is recommended that MSMEs evaluate BEP and MoS periodically to adjust their strategies to market dynamics, increase profitability, and improve business sustainability. This study provides a better basis for decision making in facing competition and market changes.